The Compositions of Thomas Tallis: How the English Reformation Informed His Style - Joshua L. Gore (Musical Offerings, 2020)
Thomas Tallis, known by some as the "Father of English Church Music," accomplished one of the most impressive feats in the history of musical service: surviving in the Chapel Royal through the reigns of vastly different monarchs during one of the most volatile political climates in the country's history. A clear streak of pragmatism shines through this stability and success, but exactly how did that pragmatism demonstrate itself within his compositional style? Through exploration and analysis of Tallis's musical style in different political and religious periods, one discovers the answer to how he managed to navigate the winds of change that led to ostracization and demise for so many leaders in the flux of power. His brilliance becomes evident as the diversity and skill with which he composed allowed the music to speak to its audience in a way that was both politically acceptable and stylistically creative. Through his adaptability and keen sense, Tallis’s compositions became exemplars for the musical principles espoused in whatever period he composed within, whether it be the austere practice of the Cranmer/Edwardian period, or the decidedly more expressive works composed under Queen Mary. The fact that his music still speaks to many today shows the legacy that this titan of church composition left behind as the nimble purveyor of distinct and period defining styles in composition.